Using Cloud Technologies To Develop The It Competence Of Future Engineers - pcadmin, Qodirov Bekmurod Nurillayevich (Genius Journals, 2025)
As part of the study, the specifics of the functioning of modern high-tech enterprises related to the organization and automation of production processes through the use of various types of information systems are analyzed, and the growing importance of cloud technologies as the optimal means of implementing these processes is determined
Keywords: cloud servers; cloud computing